Voices of the Governed: towards a theory of the translocal - Banerjee, Subhabrata Bobby (Organization (London, England), 2011)
In this article I want to interrogate the political, economic, and social conditions that enable the extraction of natural and mineral resources from Indigenous and rural communities in Africa, the Americas, and the Asia-Pacific. The end of direct colonialism and the emergence of the development state did not necessarily translate into forms of local sovereignty for these communities who bore the brunt of development. I describe the emergence of resource wars in the postcolonial era and how organizational technologies of extraction, exclusion and expulsion lead to dispossession and death. I conclude by discussing possibilities of resistance and develop the notion of translocal resistance where local actors most affected by development are able to forge a series of temporary coalitions with international and national groups in an attempt to promote some form of participatory democracy. The article advance debates on postcolonialism by developing theoretical insights from translocal modes of resistance that open up new analytical spaces marked by particular configurations of market, state and civil society actors.